Double-peaked Lyman α emission at z = 6.803: a reionization-era galaxy self-ionizing its local H ii bubble. Issue 1 (22nd October 2020) - Meyer, Romain A; Laporte, Nicolas; Ellis, Richard S; Verhamme, Anne; Garel, Thibault
ABSTRACT: We report the discovery of a double-peaked Lyman α profile in a galaxy at z = 6.803, A370p_z1, in the parallel Frontier Field of Abell 370. The velocity separation between the blue and red peaks of the Lyman α profile (Δ v=101_-19^+38 (± 48) km s^-1 ) suggests an extremely high escape fraction of ionizing photons 59(51) per cent (2σ) . The spectral energy distribution indicates a young (50 Myr), star-forming (12± 6 M_yr^-1 ) galaxy with an IRAC excess implying strong [O iii ] + H β emission. On the basis of the high escape fraction measured, we demonstrate that A370p_z1 was solely capable of creating an ionized bubble sufficiently large to account for the blue component of its Lyman α profile. We discuss whether A370p_z1 may be representative of a larger population of luminous z ≃ 7 double-peaked Lyman α emitting sources with high escape fractions that self-ionized their surroundings without contributions from associated ultraviolet-fainter sources.